THE INFLUENCE OF INFORMATION QUALITY, CONVENIENCE, PRICE AND ONLINE SHOP PRODUCT QUALITY ON CONSUMPTIVE BEHAVIOR OF FLORES UNIVERSITY OF ECONOMICS EDUCATION STUDENTS - Sayful Amrin; Stefanus H.G.Ma; Erniana Angul (Jurnal Scientia, 2023)
This study aims to determine the quality of information, convenience, price and product quality on consumptive behavior in the purchasing system using the Online Shop. This research method is quantitative by collecting data using documentation and questionnaires. The collected data were analyzed using multiple linear regression. The results of the study show (1) there is a significant influence between the information quality variable (X1) on student consumptive behavior. The results of the analysis show that the value of t count > t table is 2.131 > 1.99254 and a significant value of 0.036 <α (0.05). (2) There is a significant effect between the convenience variable (X2) on student consumptive behavior. The results of the analysis show that the value of t count > t table is 2.222 > 1.99254 and a significant value is 0.025 <α (0.05). (3) there is a significant influence between the price variable (X3) on student consumptive behavior. The results of the analysis show that the value of t count > t table is 2.609 > 1.99254 and a significant value is 0.012 <α (0.05). (4) there is a significant influence between the product quality variables (X4) on student consumptive behavior. student.